2012
DOI: 10.7439/ijbar.v3i4.398
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Use of Modified Who Partograph on Maternal and Perinatal Outcome

Abstract: Background: Early detection of abnormal progress and prevention of prolonged labour can significantly improve the outcome of labour. Partograph is an inexpensive tool which can provide a continuous pictorial overview of labour and is essential to monitor and manage labour. Objective: The study was aimed to determine if among low risk labouring women, the use of modified WHO partograph resulted in reduced maternal and perinatal morbidity Methodology: The course of labour of 100 women with uncomplicated full ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
2
27
1
Order By: Relevance
“…In present study, the various parameters recorded to substandard ranged from 5-60% of the cases, with the lowest recording of maternal urine output. It is higher than the study done in Ghana (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).5%) [15] and Kenya, most of parameters [16]. On the other hand, the study conducted in Tanzania was 86% of the cases recorded to substandard [18], which is higher than this findings.…”
Section: Discussioncontrasting
confidence: 62%
“…In present study, the various parameters recorded to substandard ranged from 5-60% of the cases, with the lowest recording of maternal urine output. It is higher than the study done in Ghana (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).5%) [15] and Kenya, most of parameters [16]. On the other hand, the study conducted in Tanzania was 86% of the cases recorded to substandard [18], which is higher than this findings.…”
Section: Discussioncontrasting
confidence: 62%
“…The present study was comparable to the study conducted by Surekha T et al who found a significant reduction in NICU admissions of control group not monitored by Partograph (17%) as compared to the cases (6%) who were monitored by modified WHO Partograph. 12 In study conducted by Ajay KS et al, there were 5.2% NICU admissions.…”
Section: Discussionmentioning
confidence: 95%
“…However, evidence from other studies indicates that partograph use may contribute to shorter labours and some improvement in maternal and fetal outcomes [18–21]. Health care workers found the modified partograph the most user-friendly version [3, 22, 23], with the latent phase of the composite partograph considered difficult to complete.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of improved outcomes for women and newborns, there is conflicting evidence as to whether the partograph works, although studies in low-resource settings suggest that it may have positive impact [18–21]. There is no evidence that partograph use is detrimental to outcomes [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation